PENGARUH MODEL PEMBELAJARAN PBL BERBANTUAN MEDIA GAMBAR TERHADAP HASIL BELAJAR IPA SISWA KELAS III SD - Ayu Ade Anjelina Putri (Universitas Pendidikan Ganesha, 2018)
The purpose of this research is to know the significant difference of science learning outcomes between the students who use problem based learning method and the students who don't use the method to the 3rd grade primary students of cluster VI, sawan distric in academic year 2017/2018. This kind of research is quasi-experimental research. The design of the research is non equevalent post test only control group design. The population of this research are all of 3rd grade primary students, cluster VI, sawan distric. There are 164 students. The samples of this research are the 3rd grade primary students of SDN 1 kerobokan. There are 18 students as samples and 23 of the 3rd grade students of SDn 4 sangsit. The method of collecting data by